THE FACTORS THAT INFLUENCE ARTIFICIAL INTELLIGENCE IMPLEMENTATION AT PT PELINDO III (Case Study in Terminal Teluk Lamong Surabaya) - pujiartini pujiartini; ulung pribadi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2020)
This study uses qualitative descriptive methods. The type of data used in this analysis is secondary data from library analysis surveys, research-related data from various sources, websites, and government documents that can facilitate the completion of this research report. In the era of globalization, all private companies and state-owned enterprises (BMUN) already have various advanced machine technology features as one of the tools that will facilitate human performance to improve the economy. As found in PT Terminal, Teluk Lamong (PT TTL) already has various tools for unloading advanced goods or known as artificial intelligence (AI). This tool can help performance and has a unique concept, namely, Go green (No pollution).